2009
DOI: 10.1128/aem.02287-08
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and Fitness of Fusarium graminearum Populations from Rice in Korea

Abstract: Fusarium graminearum is an important fungal pathogen of cereal crops and produces mycotoxins, such as the trichothecenes nivalenol and deoxynivalenol. This species may be subdivided into a series of genetic lineages or phylogenetic species. We identified strains of F. graminearum from the Republic of Korea to lineage, tested their ability to produce nivalenol and deoxynivalenol, and determined the genetic composition and structure of the populations from which they were recovered. Based on amplified fragment l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
134
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(151 citation statements)
references
References 39 publications
(39 reference statements)
11
134
2
1
Order By: Relevance
“…While the species within the FGSC show a significant biogeographic structure (Aoki et al 2012), substantial species diversity has been observed in South America (Scoz et al 2009;Sampietro et al 2010;Umpiérrez-Failache et al 2013), Asia (Yli-Mattila et al 2009Suga et al 2008;Zhang et al 2012), Africa (Boutigny et al 2011;O'Donnell et al 2008) and New Zealand (Monds et al 2005). Long-distance dispersal and anthropogenic activities have the potential to alter regional pathogen composition as suggested by the recent discovery of significant populations of F. asiaticum, an Asian endemic that appears to be adapted to rice agroecosystems (Lee et al 2009), on wheat in major rice production areas of Louisiana and Uruguay . However, climatic conditions in Norway and other parts of Northern Europe may create a barrier to the establishment of some FGSC species.…”
Section: Discussionmentioning
confidence: 99%
“…While the species within the FGSC show a significant biogeographic structure (Aoki et al 2012), substantial species diversity has been observed in South America (Scoz et al 2009;Sampietro et al 2010;Umpiérrez-Failache et al 2013), Asia (Yli-Mattila et al 2009Suga et al 2008;Zhang et al 2012), Africa (Boutigny et al 2011;O'Donnell et al 2008) and New Zealand (Monds et al 2005). Long-distance dispersal and anthropogenic activities have the potential to alter regional pathogen composition as suggested by the recent discovery of significant populations of F. asiaticum, an Asian endemic that appears to be adapted to rice agroecosystems (Lee et al 2009), on wheat in major rice production areas of Louisiana and Uruguay . However, climatic conditions in Norway and other parts of Northern Europe may create a barrier to the establishment of some FGSC species.…”
Section: Discussionmentioning
confidence: 99%
“…In our experiment this could be explained with two hypothesis: first, F. graminearum NIV chemotype, mentioned by Zhang et al (2007), is in lineage 6, so in some way they may behave differently from F. graminearum population of NorthernCentral Italy (lineage 7), exclusively isolated from durum wheat. On rice Lee et al (2009), observed that the different ecological ability between lineage 6 isolates and lineage 7 isolates were not directly related to the mechanism of pathogenicity; second, it is possible that some chemotypes of F. graminearum could be transported to other locations by seed shipping and long-distance spore transportation influencing chemotype composition (Guo et al, 2008). In fact in Western Canada, between 1998 and 2004, it was detected an increase of more than 14-fold of F. graminearum 3Ac-DON producers: that was linked to an introduction of a 3Ac-DON pathogenic population that was more toxigenic and vigorous, with a selective advantage above 15Ac-DON chemotype (Ward et al, 2008).…”
mentioning
confidence: 99%
“…Fusarium culmorum, F. poae, and F. avenaceum are observed in many European countries while F. asiaticum is observed in Asia (Waalwijk et al 2003). Fusarium graminearum and F. asiaticum, members of theet al 2014), whereas F. asiaticum is the major agent of FHB in many Asian countries such as China, Korea, Japan and Nepal (Zhang et al 2007;Karugia et al 2009;Lee et al 2009;Sarver et al 2011). FGSC possesses extremely important species which are very widespread.…”
Section: Introductionmentioning
confidence: 99%